Iron Metabolism Disturbance in a French Cohort of ALS Patients. (2nd July 2014) - Veyrat-Durebex, Charlotte; Corcia, Philippe; Mucha, Aleksandra; Benzimra, Simon; Mallet, Cindy; Gendrot, Chantal; Moreau, Caroline; Devos, David; Piver, Eric; Pagès, Jean-Christophe; Maillot, François; Andres, Christian R.; et al.
Abstract : Objective. The aim of this study was to assess iron status in a cohort of amyotrophic lateral sclerosis (ALS) patients compared to controls in order to evaluate these parameters as a risk factor or a modifying factor of ALS. Methods. We collected serum iron, ferritin, transferrin, total iron-binding capacity, and transferrin saturation coefficient (TSC) from 104 ALS patients at the time of diagnosis and from 145 controls. We reported phenotypic characteristics and evolution parameters such as ALSFRS-R and forced vital capacity at diagnosis and after one year of follow-up. In a first step we compared iron status between ALS patients and controls, and then we evaluated the relation between iron status and disease evolution of ALS patients using univariate and multivariate analysis. Results. We observed increased concentrations of serum iron (P = 0.002 ) and ferritin (P < 0.0001 ) and increased TSC (P = 0.017 ) in ALS patients. We also showed an association between markers of iron status and high body weight loss in ALS patients. The multivariate analysis of survival highlighted a significant relation between ferritin level and disease duration (P = 0.038 ). Conclusion. This is the first study showing a higher concentration of serum iron in ALS patients, strengthening the involvement of a deregulation of iron metabolism in ALS.